Pelestarian Sardundun Sebagai Budaya Masyarakat Di Desa Tanjung Bulan - Hidayatullah, Fadhilah (UNIVERSITAS INDO GLOBAL MANDIRI)
This article discusses the results of research on Sardundun's spoken literature in Tanjung Bulan village, Pulau Beringin district (OKU Selatan). The background is the need for local cultural inheritance that has a life value, but has begun to be abandoned by the community. The approach used in this research is qualitative with descriptive methods. The results of this study are to present poetry that contains elements of language and art culture that have local cultural richness in the local area. The purpose of this research is to make the public know that the province of South Sumatra has a culture in Sardundun's speech. The value contained is the principle of life that exists in a creature is to convey gratitude to the creator, which is based on conscience through the medium of the spoken language. Through inheritance, it can be done using the medium of the language spoken. However, it is not limited to oral, but written orally. Initially in the form of spoken speech, now it can only be done by means of written speech. Through local cultural inheritance, it is very appropriate to do it with written media and then tell it. Inheritance is more effectively carried out in educational institutions, because it serves as a forum for learning and teaching. Recommendations for further research, so that it can be used as material for the world of education, so that the transformation of the local Sardundun culture is carried out and its inheritance can be realized. Thus the local culture still exists and exists in the community where the speech was born, and is familiar with the community in general.